Flexible Yet Fragile: Work–Life Balance of Final-Year Students Engaged in Gig Work in Higher Education - Nayla Azka Fadila; Mimbar Oktaviana (Al-Qalam Institue, 2026)
The rapid expansion of the gig economy has reshaped student employment patterns, particularly among final-year university students who must navigate competing academic and work demands. This study aims to explore how final-year students engaged in gig work experience and negotiate work–life balance within the context of higher education. Employing a qualitative research design with a phenomenological approach, this study involved four final-year students participating in task-based or on-demand gig work. Data were collected through in-depth interviews and analyzed thematically to capture participants’ lived experiences. The findings indicate that work–life balance is perceived not as a stable or fixed state, but as a dynamic and situational process shaped by fluctuating academic workloads, job flexibility, and personal resource availability. Participants relied on psychosocial strategies such as time management, self-regulation, and social support to manage their dual roles. However, sustaining this balance often required significant personal sacrifices, including reduced rest and limited social engagement, which contributed to basic psychological need frustration and diminished well-being. These findings imply that higher education institutions need to reconsider student support systems by integrating flexible academic policies, psychosocial support services, and work-integrated learning frameworks to better accommodate the realities of student engagement in gig work.